Possession in motion: a five-season analysis of running in-possession and out-of-possession with match outcomes in the English Premier League - Allen, Tom; Taberner, Matt; Zhilkin, Mikhail; Harper, Damian; Alexander, Jill (Biology of Sport, 2026)
This study examined relationships between running load, possession metrics, and team success (points per game (PPG)), across five English Premier League (EPL) seasons (2019/20–2023/24). Comparison of running and possession demands when facing top six (T6) versus lower-ranked (7–20) opponents was also explored. Analysis of 1675 matches, using Second Spectrum® optical tracking system, to measure running load variables (total distance (TD), high-intensity distance (HID), high-speed running (HSR), sprint distance (SprD), expressed as totals, in-possession per minute (TIP), out-of-possession per minute (TOOP), and TOOP/TIP ratios. Pearson’s correlations assessed relationships between running load, possession, ball-in-play (BiP), and PPG. Differences between T6 and lower-ranked teams were assessed using Wilcoxon rank-sum tests. PPG correlated very largely with possession (r = .74, p < 0.001), and largely with TOOP/TIP ratios and BiP (r = .50–.65, p < 0.001). Moderate positive correlations with PPG were observed with TOOP metrics (r = .34–.45, p < 0.001), while SprD showed a small positive relationship (r = .25, p=0.01). TIP metrics correlated negatively with PPG (r = –.22 to –.57, p = 0.001–0.023). Against T6 teams, clubs ran more in total and TIP (ES = 0.11–0.41, p < 0.02), but less TOOP and lower TOOP/TIP ratios (ES = –0.11 to –0.54, p < 0.006), alongside reduced possession (ES = –0.96 to –1.04, p < 0.001) and PPG (ES = –0.61 to –0.66, p < 0.001). EPL success is very largely associated with possession and greater out-of-possession running, while in-possession running relates negatively. Only SprD correlated with PPG, suggesting total running load is less influential than possession and defensive running efficiency.